The effect of inner ring groove on leakage reduction in dry gas seals and its visualization verification - Ochiai, Masayuki; Ohya, Yuta (Frontiers in Mechanical Engineering, 2024)
This study investigates the impact of incorporating an Inner Ring Groove (IRG) on the leakage characteristics of dry gas seals, commonly used in turbomachinery such as gas turbines and compressors. The primary objective is to enhance sealing performance and reduce gas leakage, which is critical for improving the efficiency of these machines. The research focuses on various groove shapes, including spiral grooves for single-direction rotation and T-grooves and tree grooves for bi-directional rotation. The experimental setup involved measuring air leakage rates across different seal configurations, both with and without the IRG. The results indicated that while the IRG increased leakage in spiral groove seals, it significantly reduced leakage in T-groove and tree groove seals. Specifically, the IRG reduced leakage by approximately 26% in T-groove seals and 15.8% in tree groove seals, compared to their standard configurations. Additionally, the study employed Particle Image Velocimetry (PIV) to visualize gas flow within the seal gaps. The visualization revealed that the IRG altered the flow dynamics, particularly in T-groove seals, where it redirected the gas flow from a radial to a circumferential direction, thereby reducing leakage. In contrast, the IRG in spiral groove seals promoted radial flow, leading to increased leakage. These findings suggest that the application of IRGs can be particularly effective in bi-directional rotation seals, offering a potential design modification to enhance sealing performance. The study concludes that while IRGs may not be suitable for all groove types, their strategic application can lead to significant improvements in leakage reduction and overall efficiency of dry gas seals.